FILLING THE LEGAL VACUUM OF INDONESIAN MARKS LAW: THE LEGAL STANDING OF A FAMOUS PERSON IN SUING MARKS INFRINGEMENT - Amirulloh, Muhamad; Novianty Muchtar, Helitha; Muhtadin, Didin (Jurnal Bina Mulia Hukum, 2023)
Indonesian Marks Law in Article 21 paragraph (2) letter a has protected famous people from using their names or abbreviations as marks by other parties without permission. However, that law has not protected famous people from suing for cancellation and/or compensation against a party using the name and/or abbreviation of his name as a mark. Using the normative juridical method, the provisions on the legal basis for famous people to sue other parties who use their names or their abbreviations as marks are analyzed. This article examines legal principles and legal theories that can be used to resolve that. The results of the study conclude that the legal principles that can be used to provide a legal basis for famous people in suing other parties without permission to use their names or abbreviations as marks are the principle of good faith, the principle of legal certainty, the principle of point d' interest, point d' action, and the principle of legitima persona stands in judicio. Legal theories that can provide a legal basis for famous people in suing other parties without permission to use their names or abbreviations as marks are the welfare state theory, development law theory, and the theory of intellectual property protection from Robert M. Sherwood.